PERSONAL BRANDING I NYOMAN SUWIRTA SEBAGAI TOKOH POLITIK DALAM PILKADA KLUNGKUNG TAHUN 2018 - Pranisitha, Ayu Khania; Amanda Gelgel, Ni Made Ras; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT A Brand is not only used in marketing a product, but a brand is also used as a personality marketing for a political figure. Through this research, researchers want to see how I Nyoman Suwirta's Personal Branding as a political figure in the Klungkung Regional Election in 2018. This research is a qualitative study using Harold Lasswell's analytical method and elaborated through eight personal branding concepts from Peter Montoya. The resulst of this research that I Nyoman Suwirta has personal branding that is what it is, populist, visionary and prioritizing the public interest, as well as actively communicating through social media, and face to face with the community. That way the Klungkung community also actively participates in each Gema Santi program. Key words: Personal Branding. Regional Head Election 2018, and Political Figure.